Perlindungan Hukum Terhadap Pekerja yang Mengalami Pemutusan Hubungan Kerja Secara Sepihak Pasca Perusahaan Merger - Mirza Djafar, Aureelia Nourani; Lie, Gunardi (Universitas Ekasakti, 2023)
There are still many violations of workers' or laborers' rights that they should receive in situations where a company is merging or merging where there is legal uncertainty in protecting workers or laborers from companies that are merging or merging in violation of the 1945 Law. The aim of this research is to conduct research regarding the rights of workers or laborers who experience unilateral termination of employment by companies carrying out a merger. The method used in this research is a normative legal method with secondary data collection techniques through literature study. The results of this research show that the implementation of a company merger (merger) has a legal impact on employees, one of the impacts that can be received by employees is the loss of their job. As regulated in legal regulations both in the Limited Liability Company Law and in the Employment Law which provides legal protection for employees. . If the company does not want to take responsibility, employees can sue the company either through litigation or non-litigation.